Bukhara at the End of the XIX Century and the Beginning of the XX Century Socio-Political Situation in the Emirate - Ahmadova Zebiniso Shavkatovna (Researchparks Publishing, 2022)
In this article, the Emirate of Bukhara was a semi-colonial state dependent on Russia based on monarchical regimes in the late 19th - early 20th centuries, the radical reform of education, schools and madrasas in Turkestan, with particular attention to the modernist movement and essence of the Emirate of Bukhara, together with the political movement in the emirate, there was a talk about changing the education system, awakening the nation to the meaning, as well as the fact that Jadidism is based on world social and national values.